1993
DOI: 10.1007/bf00304623
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in ovarian follicles of Drosophila melanogaster: inhibition and promotion of dye-coupling between oocyte and follicle cells

Abstract: The analysis of chimeras has shown that communication between germ-line and soma cells plays an important role during Drosophila oogenesis. We have therefore investigated the intercellular exchange of the fluorescent tracer molecule, Lucifer yellow, pressure-injected into the oocyte of vitellogenic follicles of Drosophila. The dye reached the nurse cells via cytoplasmic bridges and entered, via gap junctions, the somatic follicle cells covering the oocyte. The percentage of follicles showing dye-coupling betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Ring canals allow for movement of macromolecules between nurse cells and from nurse cells to the oocyte (Robinson and Cooley 1996), as well as between subsets of follicle cells (McLean and Cooley 2013). In contrast, portals for exchange of components between germline and somatic cells have been thought to be limited to gap junctions, which allow only for transit of small molecules (Bohrmann and Haas-Assenbaum 1993;Zhu et al 2007). A recent report of germline-derived proteins appearing in the follicle cell epithelium independent of endocytosis raises the possibility of alternate pathways of protein exchange, although in this example the germline proteins do not appear to actually enter into individual follicle cells (Furriols and Casanova 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ring canals allow for movement of macromolecules between nurse cells and from nurse cells to the oocyte (Robinson and Cooley 1996), as well as between subsets of follicle cells (McLean and Cooley 2013). In contrast, portals for exchange of components between germline and somatic cells have been thought to be limited to gap junctions, which allow only for transit of small molecules (Bohrmann and Haas-Assenbaum 1993;Zhu et al 2007). A recent report of germline-derived proteins appearing in the follicle cell epithelium independent of endocytosis raises the possibility of alternate pathways of protein exchange, although in this example the germline proteins do not appear to actually enter into individual follicle cells (Furriols and Casanova 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although this result could be interpreted as an argument against Pipe acting as a sulfotransferase in the ovary, we do not believe this to be the explanation. Because PAPS, the product of PAPS synthetase activity, is a small molecule (507 Da), it may be able to pass through the gap junctions that exist between the oocyte and follicle cell layer (Giorgi and Postlethwait, 1985;Bohrmann and Haas-Assenbaum, 1993;Waksmonski and Woodruff, 2002). Gap junctions are known to allow passage of molecules of approximately 1 kDa in mass (Goldberg et al, 2004), which would permit passage of PAPS from a wild-type oocyte into mutant follicle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above explanations, previous investigators have suggested that a failure to observe dye coupling between insect cells can be attributed to (1) the use of an unphysiological saline (Bohrmann and Haas-Assenbaum, 1993), and (2) impalement damage that allows Ca 2+ to leak into the injected cell and close dye-permeable gap junctions (Lang and Walz, 1999). The first artifact can be ruled out in the present study, because isolated Malpighian tubules of Aedes aegypti bathed in the saline that we used in the present study secrete fluid for hours (Beyenbach and Dantzler, 1990), which would not be expected with use of an unphysiological solution.…”
Section: Permeable To Current But Not To Lucifer Yellowmentioning
confidence: 99%